Joint Editorial - Hirshleifer, David; Schwert, G. William; Singleton, Kenneth J. (Review of Financial Studies, 2013)
In 2002, the editors of the RFS, JF, and JFE simultaneously published an editorial that urged authors to make good use of the advice and input provided by referees.1 Recent informal communications have suggested to us that it is time to renew that advice. Many papers are submitted to our journals, and the scarcest resource we have as a profession is the supply of time donated by referees to read, consider, and comment on their colleagues' work. In general, the author does not know the identity of the referee, so referees can express honest opinions about the quality of the work without alienating the author. However, this system has the counterproductive consequence that authors can undervalue the services they receive.We are particularly troubled by two practices that we see too frequently. First, some authors submit papers to journals at a relatively early stage of production in the hope that “the referee will help me figure out how to revise it to make it publishable.” This strategy imposes substantial costs on both sides. It burdens the referees with responsibilities that are not theirs. For the submitter, it raises the probability that the referee and editor will reject the paper as being too distant from acceptability. By submitting a paper that is unpolished, an author can cut off a potentially valuable publication outlet.